The attenuation of legal change - Luigi Alberto Franzoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
This chapter, forthcoming in the Research Handbook on Law and Time (F. Fagan & S. Levmore eds., Edward Elgar 2024), offers a contribution to the economics of legal transition. It argues that the lawmaker should mitigate the burden generated by the risk of legal change by avoiding "extreme" decisions. The chapter puts the attenuation policy in perspective and compares it to other transition tools.
Keywords: K10; 330; legal transition; cost-benefit analysis; legal change